Exchange Rate Of Household Income Of People's Palm Oil Harvest Workers - Inayah, Fati; Reswita; Windirah, Nola; Kifli, Gontom Citoro (JURNAL AGRIBISAINS, 2025)
This study aims to analyze the household income structure of community oil palm harvest workers, analyze the consumption expenditure patterns of households of community oil palm harvest workers, analyze the exchange rate of household income of community oil palm harvest workers in Air Rami District, Mukomuko Regency. The population in this study were smallholder oil palm harvest laborers. The sample of this research was 100 households of oil palm harvest laborers. The data analysis method used in this research is descriptive quantitative, which includes analysis of the household income structure of smallholder oil palm harvest laborers, total household income of smallholder oil palm harvest laborers, analysis of consumption expenditure patterns, and analysis of the exchange rate of household income of smallholder oil palm harvest laborers. The results showed that the income structure of oil palm harvest laborer households in Air Rami Subdistrict consisted of three incomes, the total household income was Rp. 1,672,418. For the total consumption expenditure of harvest labor households is Rp. 2,165,125/month which consists of two expenses, namely food expenditure and non-food expenditure. So that the exchange rate of oil palm harvest labor household income is obtained at 0.63 or NTPRT < 1, where the welfare of oil palm harvest labor households is categorized as not prosperous. The welfare level of oil palm harvest laborer households can be categorized as prosperous, with several policies, namely that oil palm harvest laborer households must look for other jobs, for example, such as small micro businesses (processed chips, cakes, and so on) or other family members of productive age participate in working to meet household needs.